Kaposi's sarcoma: a review of gene expression and ultrastructure of KS spindle cells in vivo. - Stürzl, Michael; Brandstetter, Heinz; Roth, W K (Aids Research and Human Retroviruses, 1992)
The ultrastructural features and the gene expression pattern of Kaposi's sarcoma (KS) spindle cells in vivo suggest that KS is a tumor of the mixed cell type. The expression pattern of cytokines and cytokine receptors in the tumor lesion, together with the results obtained from in vitro characterization of KS-derived cells, provide evidence that paracrine mechanisms of growth factor action are important for the maintenance of KS. The reports on virus infection of KS cells suggest an indirect role of virus infection in the induction of KS, most likely mediated by immunostimulation and subsequent production of cytokines.